Methodology for Developing Grammatical Competence of Higher-Grade Students Based on a Communicative Approach - Odiljon kizi, Mamaziyoyeva Orzixon (Indonesian Journal Publisher, 2025)
This study ahims to develop and substantiate an effective methodology for enhancing grammatical competence of higher-grade students through a communicative approach in English laguage teaching. The research employs a qualitative descriptive and experimental design, utilizing classroom observation, comparative-logical analysis, and experimental testing to examine the effectiveness of communicative grammar instruction. Communicative tasks, inductive and deductive techniques, and interaction-based activities were implemented during the instructional process. The results indicate that integrating grammar instruction into meaningful communicative contexts significantly improves students’ grammatical accuracy, fluency, and ability to apply grammatical structures in oral and written communication. The findings further reveal that the use of role plays, information-gap activities, problem-solving tasks, and technology-supported learning enhances grammatical awareness and learner autonomy. The study concludes that the communicative approach provides an effective and pedagogically sound framework for developing grammatical competence among higher-grade students.